Associations of fruit and vegetables intakes with blood HDL cholesterol in high consumption regions of Burkina Faso - Jeoffray Diendéré; Abdoulaye Hama Diallo; Cheick Oumar Yaro; Jean Kaboré; Jérôme Winbetouréfâ Somé; Augustin Nawidimbasba Zeba (Clinical Epidemiology and Global Health)
Introduction: To report independently the sociodemographic and lifestyle parameters, the associations of fruit and vegetables intakes with blood HDL-cholesterol (HDL-C), in men and women living in high consumption areas of Burkina Faso. Methods: This was a cross-sectional secondary analysis using data from the first WHO Stepwise Approach to Surveillance (STEPS) survey conducted in Burkina Faso. The “Centre-Ouest” and “Nord” regions of Burkina Faso are identified as the areas of high fruit and vegetables consumption. Data from 602 adults living in these two regions and surveyed with the STEPS method were used. Descriptive and association analyses were performed. Results: Participants with a typical daily intake of at least two portions were 20.4 % (14.7 % in men, vs 25.6 % in women, p = 0.001) for fruit and 30.1 % (25.9 % in men, vs 33.9 % in women, p = 0.03) for vegetables. Prevalence of low blood HDL-C was 72.6 % (71.3 % in men and 73.7 % in women, p = 0.51). In logistic regressions, the daily intake of at least two portions of fruits but not at least two portions of vegetables, was associated with low odds for low HDL-C among men (aOR = 0.34, CI95 %: 0.17–0.69) and women (aOR = 0.35, CI95 %: 0.18–0.71). Similarly, the daily intake of at least three portions of fruits but not vegetables was significantly associated with low odds for low HDL-C. Conclusion: Blood HDL-C levels could be improved by eating at least two or three portions of fruit, which appears to be an achievable goal in study area. Such health benefits should not be ignored and missed.